The Influence of Environmental Performance towards Creating Shared Value - Rahardja, Liana; Gunawan, Itjang; Augustine, Yvonne; Wardhani, Ratna (Technium Social Sciences Journal, 2021)
The company performance is not about the financial performance, but also need to consider other factors, such as environmental performance and social performance. The three factors, named Triple Bottom Line (TBL) that plays an important role in the company’s performance evaluation. By applying TBL, it is believed that the company can create shared value to the stakeholders. Moreover, the topic of environmental performance and CSV is still limited especially in Indonesia. Therefore, the purpose of this research is to analyze the influence of environmental performance towards Creating Shared Value (CSV) empirically. The research sample is 29 public listed companies in Indonesian Stock Exchanges that published the sustainability reports from 2006-2014 (purposive sampling techniques). The results show that the influence of environmental performance towards CSV is not only in the short term (the current year) and but also in the long term (3-4 years later). The environmental performance would influence CSV significantly in the next 2 years, and could not influence CSV in the same year, the next 1 year, the next 3 years and the next 4 years. It indicates that the environmental activities need a longer time to influence CSV.